1989
DOI: 10.1111/j.1365-2141.1989.tb06285.x
|View full text |Cite
|
Sign up to set email alerts
|

Human monoclonal anti‐D antibodies. I. THEIR PRODUCTION, SEROLOGY, QUANTITATION AND POTENTIAL USE AS BLOOD GROUPING REAGENTS

Abstract: Eight monoclonal IgG antibodies to the Rh antigen D, produced by Epstein-Barr virus transformed B-lymphoblastoid cell lines from two individuals, have been assessed for their suitability as blood grouping reagents. All showed similar specificity and agglutinated all red cells with partial D antigens tested except category DVI cells. They gave strong reactions with Du red cells in indirect antiglobulin tests, and they all gave good reactions with R1R1, R2R2 and R0r cells in manual tests using antiglobulin, enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(41 citation statements)
references
References 13 publications
0
40
0
1
Order By: Relevance
“…The production of human monoclonal anti-D antibod ies by long-term culture of Epstein-Barr virus (EBV)-transformed lymphocytes has recently been described [1][2][3][4][5]. In the future, it may be possible to use these antibodies for prophylaxis against haemolytic disease of the newborn.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of human monoclonal anti-D antibod ies by long-term culture of Epstein-Barr virus (EBV)-transformed lymphocytes has recently been described [1][2][3][4][5]. In the future, it may be possible to use these antibodies for prophylaxis against haemolytic disease of the newborn.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…The serological characteristics of some of these antibodies have recently been described [5]. The IgG subclasses were determined by haemagglutination using subclass specific monoclonal antibodies (Unipath).…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…The MAb-D cell lines were produced by transforming B cells from hyper-immu nised anti-D donors with the Epstein-Barr virus [16,26]. Cells were grown in static culture flasks at 37°C in RPMI 1640 medium contain ing 10% bovine IgG-depleted fetal calf serum (FCS), L-glutamine and antibiotics (Hyclonc Europe Ltd, Cramlington, UK) (RPM1/FCS) for a minimum of 10 days.…”
Section: Antibody Preparationmentioning
confidence: 99%
“…[9][10][11][12][13] With respect to AITP, however, only one study attempted to treat patients with AITP with MoAnti-D, but platelet counts were not increased. 14 It was suggested that the failure was the result of the monoclonal preparation missing factors present in polyclonal anti-D. 15 Subsequently, few studies attempted to understand why MoAnti-D preparations are not effective in AITP.…”
Section: Introductionmentioning
confidence: 99%